2020
DOI: 10.3390/su12051943
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of R&D Expenditures on Corporate Performance: Evidence from Slovenian and World R&D Companies

Abstract: Research and development (R&D) investment is widely recognised as one of the crucial elements of generating the competitive advantage of contemporary companies. At the same time, it is also considered to represent one of the key determinants of overall sustainable development. Global competition, which is becoming increasingly harsh and forces companies to provide value-added products, processes and services, constitutes a reason why R&D investment is indispensable in contemporary business operations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 59 publications
0
24
0
Order By: Relevance
“…Consistent with prior research in this area and the effort to exclude alternative explanations, this study included the following control variables: Firm size, fixed asset turnover, market competition, firm age, state ownership, and sales growth. Given that larger firms may have more favorable access to capital and more resources to generate high performance than smaller firms (115,116), we controlled for the firm size, as measured by the natural logarithm of the total assets. We operationalized firm age, which may account for a firm's experience (117,118), as the number of years since a firm was founded.…”
Section: Control Variablesmentioning
confidence: 99%
“…Consistent with prior research in this area and the effort to exclude alternative explanations, this study included the following control variables: Firm size, fixed asset turnover, market competition, firm age, state ownership, and sales growth. Given that larger firms may have more favorable access to capital and more resources to generate high performance than smaller firms (115,116), we controlled for the firm size, as measured by the natural logarithm of the total assets. We operationalized firm age, which may account for a firm's experience (117,118), as the number of years since a firm was founded.…”
Section: Control Variablesmentioning
confidence: 99%
“…Through analyzing the link between R&D investments and fair value in the advanced nations, including America, Japan, and Germany, Bae (2003) believed there is a positive correlation, while the degree fluctuated among different countries [6]. However, Ravšelj and Aristovnik (2020) concluded that no significant relationship exists between short-term corporate valuation and R&D investments, while there is a positive link among its financial performance counterparts [11]. Differently, according to Biswas (2021), R&D investments are vital for the corporations to innovate and maintain competitiveness.…”
Section: Randd Investments Impact On the Healthcare Industrymentioning
confidence: 99%
“…To exclude other explanations, there are five control variables in the research. Firstly, larger companies have more channels and resources, so they can enjoy economies of scale and are easier to generate capital as well as enhance industry barriers; hence, firm size is controlled applying log coefficients of total assets [11,18]. Secondly, a higher fixed asset turnover will be in favor of productivity and performance; thus, this research controls fixed assets turnover [18].…”
Section: Control Variablementioning
confidence: 99%
See 1 more Smart Citation
“…In order to achieve competitive advantage, efficiency and productivity of R&D operation is acquired (Werner and Souder, 1997). Although some empirical studies argue that expenditures on R&D have an immediate positive impact on current operating performance (Apergis and Sorros, 2014), while other studies argue that benefits can be visible in the long run (Gumus and Celikay, 2015;Ravšelj and Aristovnik, 2020), general opinion is that expenditures on R&D positively affect modern businesses and economic growth. One of the most important components of economic growth is technological development and therefore efficiency of R&D operations is crucial for companies, institutions and countries to be competitive A.…”
Section: Introductionmentioning
confidence: 99%